Examining the Role of Synthetic Biology in Cellular Restoration Mechanisms - Arbaz Raza Khan (International Journal of Cell Biology and Cellular Functions, 2024)
Synthetic biology has emerged as a transformative field with the potential to revolutionize cellular repair mechanisms, offering innovative solutions to repair damaged DNA, stabilize proteins, regenerate tissues, and treat a wide range of diseases. By combining principles from genetic engineering, biotechnology, and computational biology, synthetic biology enables the design of cellular systems capable of performing functions that repair cellular damage and restore normal cellular processes. This article explores the application of synthetic biology in cellular repair, focusing on key areas, such as genome editing, protein stabilization, tissue regeneration, and the development of synthetic materials. We also examine the challenges and ethical considerations associated with these technologies. Additionally, we present experimental studies on genome editing tools, synthetic chaperones for protein aggregation, and engineered tissues using synthetic biomaterials. While progress in the field has been substantial, significant challenges remain in optimizing these approaches for clinical use, including overcoming issues related to off-target effects in genome editing and the integration of synthetic systems into existing biological environments. Moreover, careful consideration of the ethical, social, and regulatory dimensions of synthetic biology is essential to promote its responsible development. The potential of synthetic biology in cellular repair mechanisms is vast, offering new possibilities for regenerative medicine, personalized therapies, and long-term health solutions.
Keywords: DNA; Medicine; Synthethic biology; cellular; tissue